Development of lightweight concrete blocks using construction and demolition waste, and thermoelectric ash (COLOMBIAN JOURNAL OF ADVANCED TECHNOLOGIES, 2023)
Construction and demolition waste (RCD) represents a serious global environmental problem, due to its high volume and impact on our environment. This paper shows the manufacture of concrete blocks using RCD, both an ecological and economical option that could minimize the amount of waste that ends up in landfills and reduce the exploitation of new natural materials. In Colombia, especially in the department of Norte de Santander, RCD management poses significant challenges, although efforts are being made to improve its management and promote a circular economy in the construction sector. The goal of this research was to incorporate RCD and ash from thermoelectric plants into the aggregate mix for the manufacture of concrete blocks in the metropolitan area of Cúcuta, in order to promote sustainability in the construction sector and minimize the environmental impact of construction and demolition waste. It is hoped that this study will encourage the use of RCD in the creation of concrete blocks both in Colombia and throughout Latin America.
Keywords: RCD; Recycled concrete; Circular economy; Light concrete